Analysis on Electrofuels in Future Energy Systems: A 2050 Case Study. (15th May 2020) - Lester, Mason Scott; Bramstoft, Rasmus; Münster, Marie
Abstract: A radical adjustment to current energy systems will be imperative in achieving the Paris Agreement. This paper analyses the holistic 2050 Danish energy system and particularly its future transport sector, which aims to be fossil fuel independent. Using a linear optimisation tool (Balmorel-OptiFlow), the role of electrofuels is analysed at a high temporal and geographic resolution for the Nordic + German region. Electrofuel technologies have been investigated and incorporated into the energy model creating a comprehensive catalogue of alternative fuel pathways. Results reveal an energy system with a high reliance on variable energy sources. Electrofuels that utilise biomass have been found to be more economically attractive compared to electrofuels using carbon capture. Biomass costs, fuel demands, and electricity prices drive the competition between the evaluated alternative fuel pathways. Carbon capture technologies are found to not play a role in the production of transport fuels unless future biomass resources are more limited or costly than expected. Additionally, it has been found that temporal resolution can greatly affect results when modelling alternative fuel pathways. The study concludes that electrofuels - particularly those using biomass - can play a prominent role in future transport sectors. Highlights: Electrofuels have high use potential in future transport systems. Fuels using hydrogen can be more economically attractive compared to biofuels. Modelling of electrofuels in holistic energy systems enables sector coupling. Novel modelling of electrofuels with high temporal and spatial resolution. Linkage of power market model and detailed spatiotemporal network model.